POETICS AND ETHICS. THE DOSCOURSE OF THE FRANCOPHONE AUTHOR FACING THE IDEOLOGIES OF BELONGING. BRITTANY, QUEBEC, “AFRICAS” - (:unkn) unknown (My University, 2008)
After having revisited the concept of authorship and analyzed the highly polyphonic and multicultural vocation of the francophone discourse, this work, focusing on three geographical areas (Brittany, Québec, Sub-Saharian Africa) and three authors (Pierre-Jakez Hélias, Félix Leclerc and Cheikh Hamidou Kane), examines the tension between the moral duty of belonging to a minority culture and the universality of the literary project. First, a study of Pierre-Jakez Hélias shows the underexamined biculturalism of some French populations and the uneasy identity of the author in a “French Francophone” context. Then, through Felix Leclerc 's writings, I question the Quebecois author's wor k, whose troubling ambiguity is not entirely accounted for by the myth of a bipolar opposition between English and French. Finally, with the study of potential identities in Kane's novels, I discuss the evidence of a homogeneous black African identity, in order to better assess the relevance of a manifold reading of African cultures in literature. Ultimately, this work demonstrates that Francophone authors are ethically free to overcome biological constraints so their work can bear the hallmark of an assumed “alterculturality”.
Keywords: African Research